Active meat packaging from thermoplastic cassava starch containing sappan and cinnamon herbal extracts via LLDPE blown-film extrusion. (December 2020) - Khumkomgool, Aruchida; Saneluksana, Thanaporn; Harnkarnsujarit, Nathdanai
Highlights: Active packaging from conventional blown extrusion of herb compounding TPS/LLDPE. Films with sappan and cinnamon gave antimicrobial and preserved redness of beef. Cinnamon gave higher compatible nano- and micro-structures between starch and LLDPE. Abstract: Compounding of starch and herbal extracts containing antimicrobial functions possibly produces active packaging to preserve food quality. Active meat packaging was developed from thermoplastic starch (TPS) containing herbal extracts namely sappan or cinnamon powders via LLDPE blown-film extrusion. Higher TPS and herbal contents caused dispersion of clumps within film matrices, giving decreased mechanical properties (60–80 % for tensile strength and 30–90 % for elongation at break) due to non-homogeneous microstructures. Surface topography indicated increased roughness by 2.0–4.0 times with addition of TPS and herbal extracts and revealed nanovoids in films containing high sappan contents. Infrared spectra indicated hydrogen bonding between starch and herbal extracts which limited disruptions of starch granules during extrusion. Increased TPS raised water vapor permeability (WVP) but decreased oxygen permeability (OP) due to increased hydrophilicity of the film matrices. Cinnamon gave higher WVP (1.7–2.0 times) than sappan but similar OP. Increased herbal contents at 2 times increased OP by 1.8–2.9 times due to the formation of microvoids. Furthermore, films were used as minced beef packaging (direct contact) and determined for meat appearance and microbial counts. Films containing ≥ 8.6 % sappan and ≥ 6.7 % cinnamon showed preserved redness of packaged minced beef due to phenolic interaction. Moreover, films containing ≥ 3.3 % herbal extracts (sappan and cinnamon) gave lower total microbial counts in packaged meat due to antimicrobial capacity of sappan and cinnamon extracts, prolonging the shelf-life of minced beef. TPS films containing sappan and cinnamon extracts effectively preserved redness and delayed microbial growth, producing active packaging.